PRAWO I ETYKA W MEDYCYNIEAre patients informed about the degree of risk of an operation suggested by the doctor? - Wroński, Konrad; Cywiński, Jarosław; Depta, Adam; Bocian, Roman; Dziki, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: One of the basic patients’ rights is the right to be informed about the degree of risk of an operation suggested by their doctors. The law referring to this right was written in the National Health Service Institutions Act, the Medical Professions Act and in the Code of Medical Ethics. Objectives: The purpose of this research was to evaluate whether doctors respect patients’ right to information about the degree of risk of an operation. Material and Methods: A group of 500 patients staying in Pirogow Hospital in Łódź was requested to fill in a survey prepared by the authors, in which tools were used to examine doctors’ respect of patients’ right to information about the degree of risk of an operation. The patients who were questioned had been operated on in different hospitals. The necessary calculations were done by means of STATISTICA 7.1 and EXCEL 2008. Results: The analysis of the research shows that 491 (98.2%) of the respondents received full information about the kind of surgery to be conducted. Among the 500 respondents, 322 (64.4%) answered that they had received full information about the degree of risk of the operation recommended by their doctor, whereas 178 (35.6%) claimed they had not been informed about the risk at all. Conclusions: Patients’ right to receive information about the degree of risk of their surgery is one of the basic rights appertaining to a patient. A lack of such information results in the fact that a patient has not received full information as to a planned operation, and his/her agreement to the surgery is invalid. A doctor performing an operation without a patient’s agreement may be sued by the patient for damages on the basis of acts written in the civil code.